Impact of the Central Bank's Communication on FX Market Dynamics - Tetiana Yukhymenko; Oleh Sorochan (Visnyk of the National Bank of Ukraine)
This study explores the impact of central bank communications on FX market dynamics. Our main results suggest that the NBU’s statements and press releases on monetary policy issues do indeed matter. We find that exchange rate movements and volatility are negatively correlated with the volumes of publications by the NBU on its official website. However, this effect is noticeably larger for volatility than for exchange rate changes. The impact of communications on FX developments is strongest a week after a news release, and it persists further. Furthermore, these indicators turn out to be more sensitive to monetary policy announcements than NBU updates overall.